2022
DOI: 10.17135/jdhs.2022.22.2.67
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Depression and Cognitive Function on the Geriatric Oral Health Assessment Index in the Elderly

Abstract: Background: Depression and cognitive function have a positive effect on the improvement of quality of life and extension of lifespan in the elderly. In addition, it appears as a major factor influencing oral health status. Therefore, this study looked at the relationship between the Geriatric Oral Health Assessment Index (GOHAI), depression, and cognitive function in the elderly using the Korea Longitudinal Study of Aging. Methods: In this study, 4,535 elderly people aged 65 years and over were targeted using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
(27 reference statements)
0
1
0
Order By: Relevance
“…Of particular, studies using KLoSA have identified irregularity in working hours [ 31 ], low life satisfaction [ 32 ], decreased chewing function [ 33 ], and the risk factors of cardiovascular diseases (CVD), such as age, diabetes, and hypertension [ 34 ], are associated with the development of cognitive impairment. It was also reported that depression and cognitive function are associated with oral health-related quality of life in elderly people aged 65 years and over using the 7th wave of KLoSA data [ 35 ]. However, a scarce number of studies exploring the association among oral health, systemic health, sociodemographic factors, as well as cognitive function altogether in elderly people have been introduced yet.…”
Section: Introductionmentioning
confidence: 99%
“…Of particular, studies using KLoSA have identified irregularity in working hours [ 31 ], low life satisfaction [ 32 ], decreased chewing function [ 33 ], and the risk factors of cardiovascular diseases (CVD), such as age, diabetes, and hypertension [ 34 ], are associated with the development of cognitive impairment. It was also reported that depression and cognitive function are associated with oral health-related quality of life in elderly people aged 65 years and over using the 7th wave of KLoSA data [ 35 ]. However, a scarce number of studies exploring the association among oral health, systemic health, sociodemographic factors, as well as cognitive function altogether in elderly people have been introduced yet.…”
Section: Introductionmentioning
confidence: 99%